Kolintang Symbolic Construction of The Union Odd Numbers (Three) in Socio-cultural Meaning of Minahasa Community - Glenie Latuni; Jultje Rattu; Ambrose Loho; Sam Saroinsong; Marlyn Windewani (Universitas Negeri Medan, 2023)
This research examines the construction of Kolintang through the symbol of the number Three in the socio-cultural life system of the Minahasa people, whose embodiment in Kolintang music. A qualitative method through a historical approach in social and anthropological writing is used in this research. The data sourcewas obtained from field observations for approximately three years in Lembean Village, namely Nine taranak or Minamerot.Interviews and recordings do well; researchers are also active in direct observation. The research found that the number one is a transcendent and intangible symbol, the God of the Minahasa people Empung, WailanWangko, EmpungRenga-Rengan, God is Glorious, God is Great. The number one does not appear in the form of kolintang but is unifying. The number three is seen in the three forms of the Minahasa grandmothers Karema, Lumimuut, and Toar; also in the three Minahasa leaders, Tunduan/Tonaas, Wadian/Walian, and Teterusan. It is seen in the three first descendants of Minahasa, namely the Tombulu, Toutewoh, and Tounsawang sub-ethnicity. This symbolisation can be seen in the construction of Kolintang instruments using three wooden sticks (Teken) singing Tatembaken, the use of three-wood Kolintang in Waleposan, and traditional modes/scales such as (1 - 2 - 3) as well as the use of three wood in modern Kolintang Music Accompaniment called Wooden Kolintang Music Ensemble (AMKK). In conclusion, the construction of Kolintang music is a form of symbolisation of the Unification of the number three in the social and cultural life of the Minahasa people.